Inheritance of gusjigang value in the young generation in environment of Jenang MSME Kaliputu Village - Firdausiyah, Faristin; Juhadi, Juhadi; Pujiati, Amin (Universitas Negeri Semarang, 2021)
The development of information and communication technology has caused the disappearance of the noble values ​​in the local wisdom. The fading of these values ​​can be overcome through the inheritance of noble values ​​from the older generation to the younger generation. One of the local wisdom in Kudus is Gusjigang. This philosophy of life from Sunan Kudus is used as a guide in everyday life. This study uses a qualitative approach. This study focuses on the inheritance of the value of local wisdom of the Kudus community, namely the value of Gusjigang, especially description of Gusjigang in the young generation of jenang MSME Kaliputu Village, the form of inheritance of these values ​​to the younger generation and the younger generation in interpreting after inheritance. The results of this study indicate that the younger generation interprets Gusjigang as an attempt to become a human being with a good personality, diligent in recite and studying and smart in trading. The form of inheritance of Gusjigang values ​​to the younger generation in environment of Jenang MSME Kaliputu Village through family and community. However, as an instruction, it requires the role and guidance of parents, the community, and the Gusjigang museum of media. Furthermore, the generations interpret every activity carried out and exemplified by their closest environment regarding Gusjigang that Gusjigang becomes a very important guide and direction in daily life which aims to live in the world and in the hereafter to be good, calm, peaceful, and his life be a blessing.